Tourism in India: A Review to Find out the Possibility for Future Growth in GDP besides Job Opportunities (International Journal of Innovative Research in Engineering & Management, 2021)
Tourism is considered as a livelihood at many parts of the world  and most beautiful thing is that many unskilled people can also  earn a good amount of money through serving the tourist. There  are many countries which are having a beautiful places and  weather but lacking behind in industrialization from rest of the  world, tourism business is a boon for them. India’s tourism  business is also depending upon its high culture, heritage, historical places, wild life, medical facilities etc. After starting  of Incredible India, Tourism business has grown multifold. The  aim of the present paper has to cover the type of the tourism  available in India and also review their impact on number of  tourists who attract towards India for travelling. The aim of the  paper is to find the future of tourism in India and how much  this sector can grow to contribute more and more In India’s  GDP and how this sector solves the problem of unemployment  in India.
Keywords: Business; Culture; Heritage; Medical; Wild life